Collagens in primary frozen shoulder: expression of collagen mRNA isoforms in the different phases of the disease. (21st December 2020) - Marker, Line; Schjerling, Peter; Mackey, Abigail L; Hansen, Thomas; Jakobsen, Jens; Kjær, Michael; Krogsgaard, Michael R
Abstract: Objectives: Primary frozen shoulder (pFS) has three phases that differ in clinical presentation. It is characterized by contracture of the joint capsule. We hypothesized that there is a general upregulation of collagens in pFS, and that this is highest in the first phase of the disease. The aims of this study were to investigate the expression of various collagens and degradation of collagens in patients with primary pFS and relate this to the three phases of the condition. Methods: From twenty-six patients with pFS and eight control patients with subacromial impingement, biopsies were obtained during shoulder arthroscopy from the middle glenohumeral ligament and the anterior capsule, and mRNA levels for collagens, MMP-2 and -14 and TGF-β1, - β2 and -β3 in the tissue were analysed using real-time PCR. Results: Genes for collagens type I, III, IV, V, VI and XIV, were activated in pFS, and the total mRNA for all collagens was increased ( P < 0.05). This upregulation was independent of disease phases in pFS. In addition, MMP-2, MMP-14, TGF-β1 and TGF-β3 were upregulated in all phases of the disease. Conclusion: There is a general upregulation and an increased degradation of collagens in pFS in all three phases of the disease. This indicates a constantly increased turnover of the fibrotic tissue in the capsule from pFS. The difference in clinical presentation of pFS observed in the three phases of the disease is not primarily a result of variations in collagen production.